The rehabilitative effects on written language of a combined language and parietal dual-tDCS treatment in a stroke case. - De Tommaso, Barbara; Piedimonte, Alessandro; Caglio, Marcella M.; D'Agata, Federico; Campagnoli, Marcello; Orsi, Laura; Raimondo, Simona; Vighetti, Sergio; Mortara, Paolo; Massazza, Giuseppe; Pinessi, Lorenzo (Neuropsychological Rehabilitation, 2017)
In this paper we report the effect of a combined transcranial direct current stimulation (tDCS) and speech language therapy on linguistic deficits following left brain damage in a stroke case. We show that simultaneous electrical excitatory stimulation to the left and inhibitory stimulation to the right parietal regions (dual-tDCS) affected writing and reading rehabilitation, enhancing speech therapy outcomes. The results of a comparison with healthy controls showed that application of dual-tDCS could improve, in particular, sub-lexical transcoding and, specifically, the reading of non-words with increasing length and complexity. Positive repercussions on patient's quality of functional communication were also ascertained. Significant changes were also found in other language and cognitive tasks not directly treated (comprehension and constructive apraxia).